Transcript variants of long-chain acyl-CoA synthase 1 have distinct roles in sheep lipid metabolism - Cao, Yang; Yu, Yongsheng; Zhang, Lichun; Liu, Yu; Zheng, Kaizhi; Wang, Sutian; Jin, Haiguo; Liu, Lixiang; Cao, Yang (Frontiers in Genetics, 2022)
Mutton has become a consumer favorite in recent years, and intermuscular fat is the key factor to determine the tenderness of meat. Long-chain acyl-CoA synthetase 1 (ACSL1) is one of the vital subtypes of ACSLs family involved in the synthesis of lipid from acyl-CoA and fatty acid oxidation. The amplification of ACSL1 gene utilizing rapid amplification of cDNA ends revealed that alternative polyadenylation (APA) results in two transcripts of the ACSL1 gene. Prematur termination of transcription was observed in exon 18, forming a shorter CDS region. The presence of at least two transcripts with different lengths which can be translated normally anddefined as ACSL1-a and ACSL1-b was confirmed in the present study. Overexpression of ACSL1-a can promote intracellular diglyceride synthesis, moreover ACSL1-b can promote triglyceride synthesis. The transfection of ACSL1 shRNA knocks down both the transcripts, the triglyceride content was significantly reduced post- induction of the differentiation. The results of the present study indicated that the ACSL1 gene played an crucial role in the synthesis of triglycerides. Furthermore, the two transcripts involved in various interactions in the triglyceride synthesis process can be the topic of interest for future studies and provide more theoretical basis for breeding of sheep.